INCREASING CUSTOMER LOYALTY THROUGH CO-CREATION, PRODUCT INNOVATION, SOCIAL MEDIA MARKETING WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Hanafiah, Hafidz; Gursida, Hari; Muharam, Hari (Yayasan Education and Social Center, 2025)
Coffee shop is a meeting place where interaction occurs between two human beings with various purposes and reasons. The phenomenon of the emergence of coffee shops in Serang City has made coffee shop managers focus on Gen Z to have their own uniqueness in creating customer loyalty through co-creation and product innovation for coffee shop managers in the era of technology and digitalization. Differences in perceptions of cafes, coffee shops, and coffee shops among Gen Z make them not loyal to coffee shops. Initial research found that customer loyalty in six coffee shops that had not been segmented for Gen Z resulted in a low level of loyalty. There is a problem with customer loyalty so that research is needed on loyalty in six coffee shops that do not yet have a Gen Z segment in Serang City. Among them are Kiri coffee, Cruz coffee, carios.id, Kopi Rona, Jannor Coffee, and also Kiara Coffee. This study aims to determine efforts to increase customer loyalty through co-creation, product innovation, and social media marketing, as well as customer satisfaction as an intervening variable. This study uses a survey method with data collection through questionnaires distributed to 400 respondents of Gen Z coffee lovers in six coffee shops in Serang City, Banten, which do not yet have a segmentation among Gen Z. This study uses a quantitative research method. The type of design that will be analyzed using the help of Structural Equation Modeling (SEM) software. The results of the analysis show that of the 100 indicators used, all are valid and reliable. Co-creation, product innovation, and social media marketing have a significant influence on customer satisfaction with a determination of 66.5%, where co-creation is the dominant factor. In addition, customer loyalty is significantly influenced by customer satisfaction, co-creation, product innovation, and social media marketing with a determination of 76.3%. This study proves that the co-creation coffee innovation model significantly increases customer loyalty in Coffee Shops in Serang City. These results provide theoretical, practical, and managerial implications, especially for coffee shop business actors in Serang City, to increase customer loyalty and business sustainability in this coffee shop.